A high interfacial bonding strength anti-peeling polyamide composite film and a preparation method thereof

CN122998995APending Publication Date: 2026-10-30TAIZHOU HEYI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611467472.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种高界面结合力的抗剥离聚酰胺复合膜及其制备方法,以解决现有聚酰胺复合膜中多孔支撑层亲水改性剂极易流失以及聚酰胺分离层界面结合力弱、易剥离的技术问题

Benefits of technology

首先,本发明基于包合与氢键锚固机理,有效解决了多孔支撑层中亲水添加剂极易流失的工业难题。通过上述分子层面的协同网络,极大地束缚了两亲性聚合物的水溶流失倾向。实验测试表明,相较于仅添加纯两亲性嵌段共聚物的对比例复合膜,本发明实施例的复合膜在经过连续长达 30 d 的错流过滤操作后,纯水通量衰减率降低至 5% 以内,展现出极佳的亲水持久性与孔隙稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998995A_ABST
    Figure CN122998995A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high interfacial bonding force anti-peeling polyamide composite film and preparation method thereof.The preparation method includes: dissolving base polymer, amphiphilic block copolymer and cyclodextrin compound in organic solvent to obtain blend casting solution;The blend casting solution is coated on the substrate and is converted by coagulation bath to obtain modified porous support layer;Then, the surface of the modified porous support layer is coated with an aqueous solution containing amine monomer and an organic phase solution containing acyl chloride monomer, interfacial polymerization occurs to generate a polyamide separation layer, and the finished product is obtained after heat treatment.The application adds amphiphilic block copolymer and cyclodextrin compound in casting solution, uses the synergistic anchoring effect of both in phase inversion process, adjusts the monomer diffusion rate, greatly improves the interfacial bonding force between the polyamide separation layer and the support layer, and makes the film material have excellent anti-delamination and peeling resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of separation membrane material manufacturing technology, specifically relating to a peel-resistant polyamide composite membrane with high interfacial bonding strength and its preparation method. Background Technology

[0002] Polyamide composite membranes are currently the most widely used separation membrane materials in the water treatment field. These membranes typically employ a solvent-inducible phase separation method to prepare a porous polyethersulfone or polysulfone support layer, followed by interfacial polymerization to generate an ultrathin, dense polyamide separation layer on the surface of the porous support layer. The polyamide layer possesses extremely high salt rejection, while the porous support layer provides the necessary mechanical strength and water flow channels. However, traditional polyamide composite membranes face the severe challenge of insufficient interfacial bonding in practical applications. Most existing commercial substrate membranes are highly hydrophobic, resulting in a weak physical interlocking bond between the polyamide layer generated through interfacial polymerization and the substrate membrane. As noted in Progress in Polymer Science, 2021, 122, 101451, this simple physical adhesion, under long-term high operating pressures of 1.5–8.0 MPa and frequent physical backwashing conditions, easily leads to large-area bubbling and delamination defects in the polyamide separation layer, resulting in a significant deterioration in the desalination performance and water flux of the composite membrane.

[0003] To improve the hydrophobicity of the support layer and indirectly enhance interfacial bonding, direct blending of amphiphilic block copolymers in the casting solution is a common industrial modification strategy. For example, the literature Journal of Membrane Science, 2006, 282, 44-51 discloses a modification method that blends Pluronic F127 with hydrophilic segments into a polyethersulfone casting solution. Although this method effectively improves the hydrophilicity of the support layer in the early stages of film formation, it faces a severe problem of additive loss. Due to the strong water solubility of Pluronic F127, a large amount of unanchored Pluronic F127 dissolves and is lost during the phase transformation in the coagulation bath and the subsequent cross-flow filtration operation lasting 30-60 days. This irreversible loss not only leads to the collapse of the support layer pores and rapid decline in hydrophilicity, but also fails to provide a durable and stable hydrophilic interface for interfacial polymerization, and the peel resistance of the composite membrane remains substantially unimproved.

[0004] On the other hand, the difficulty in controlling the diffusion rate of amine monomers during interfacial polymerization is also a significant reason for the weak bonding of the separation layer. To regulate the microscopic processes of interfacial polymerization, some studies have begun to explore the introduction of macrocyclic compounds as aqueous phase additives. For example, the literature *Chemical Engineering Journal*, 2024, 492, 152165, reports a method for preparing composite membranes by introducing β-CD into an aqueous solution to participate in interfacial polymerization. This method utilizes the unique cavity structure and hydroxyl-rich outer surface of β-CD to regulate the monomer reaction rate. However, this traditional process of directly dissolving the modifier in the aqueous phase has significant drawbacks. The modifier mainly remains free at the water-oil interface and cannot form an effective physical anchoring bridge between the porous support layer and the polyamide separation layer. When subjected to strong water flow shear forces, the weak bonding surface between the separation layer and the substrate is easily broken, failing to meet the stringent requirements for membrane mechanical stability in high-pressure fluid separation processes.

[0005] In summary, existing polyamide composite membrane modification technologies face insurmountable physical bottlenecks in addressing the loss of hydrophilic agents in the support layer and improving interfacial adhesion. Using Pluronic F127 alone in the casting solution fails to completely resolve the water washing loss problem, while simply adding macromolecules such as β-CD to the aqueous phase of interfacial polymerization cannot establish a robust upper and lower layer anchoring network. Developing an extremely simple preparation method that completely overcomes the loss defects of amphiphilic polymers in the substrate membrane without adding complex crosslinking agents, while simultaneously utilizing a modified substrate membrane to in-situ control and strongly anchor the interfacial polymerization process, thereby preparing a polyamide composite membrane with both high throughput and extremely strong anti-peeling properties, is a pressing technical challenge in the current separation membrane manufacturing industry. Summary of the Invention

[0006] The purpose of this invention is to provide a peel-resistant polyamide composite membrane with high interfacial bonding strength and its preparation method, so as to solve the technical problems of easy loss of hydrophilic modifier in the porous support layer and weak interfacial bonding strength and easy peeling of polyamide separation layer in existing polyamide composite membranes.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a peel-resistant polyamide composite film with high interfacial adhesion includes the following steps: S1, the matrix polymer, amphiphilic block copolymer and cyclodextrin compound are mixed and dissolved in an organic solvent to obtain a blend casting solution; S2, the blended casting solution is coated onto the substrate and then placed in a coagulation bath to undergo a non-solvent-induced phase transformation to form a film, thus obtaining a modified porous support layer; S3, an aqueous solution containing amine monomers is coated onto the surface of the modified porous support layer. After removing the excess aqueous solution, the surface of the modified porous support layer is brought into contact with an organic solution containing acyl chloride monomers to undergo an interfacial polymerization reaction to generate a polyamide separation layer. After heat treatment, a peel-resistant polyamide composite film with high interfacial bonding is obtained.

[0008] Preferably, the matrix polymer is selected from polyethersulfone or polysulfone; the organic solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide.

[0009] Preferably, the amphiphilic block copolymer is a poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer; the cyclodextrin compound is selected from one or more of β-cyclodextrin, hydroxypropyl-β-cyclodextrin or methyl-β-cyclodextrin.

[0010] Preferably, the mass fraction of each component in the blend casting solution is: 12-20 wt% matrix polymer, 0.5-5.0 wt% amphiphilic block copolymer, 0.5-5.0 wt% cyclodextrin compound, and the balance being organic solvent; the mass ratio of the amphiphilic block copolymer to the cyclodextrin compound is 1:0.5-1:2.0.

[0011] Preferably, in step S2, the substrate is polyester nonwoven fabric; the coagulation bath is deionized water, and the temperature of the coagulation bath is 15~30℃.

[0012] Preferably, before step S3, the modified porous support layer obtained in step S2 is immersed in deionized water for 12-48 hours to wash away residual solvent on the surface.

[0013] Preferably, the amine monomer in the aqueous solution is selected from one or more of piperazine, m-phenylenediamine, or p-phenylenediamine; the acyl chloride monomer in the organic solution is trimesoyl chloride; and the solvent of the organic solution is selected from one or more of n-hexane, isoalkanes, or n-heptane.

[0014] Preferably, the mass fraction of amine monomers in the aqueous phase solution is 0.1~2.0 wt%; and the mass fraction of acyl chloride monomers in the organic phase solution is 0.05~0.5 wt%.

[0015] Preferably, in step S3, the contact time between the aqueous solution containing amine monomers and the modified porous support layer is 1-5 min; the contact time between the organic solution containing acyl chloride monomers and the modified porous support layer is 10-60 s; the heat treatment temperature is 60-100 ℃, and the heat treatment time is 2-10 min.

[0016] The present invention also provides a peel-resistant polyamide composite membrane with high interfacial bonding strength prepared by the above preparation method. The peel-resistant polyamide composite membrane with high interfacial bonding strength includes a modified porous support layer and a polyamide separation layer bonded to the surface of the modified porous support layer. The matrix of the modified porous support layer contains an amphiphilic block copolymer and a cyclodextrin compound.

[0017] The mechanism of action of this invention is as follows: During the preparation stage of the blend casting solution, the internal cavities of the cyclodextrin compound can recognize the hydrophobic segments, such as polypropylene oxide segments, in the amphiphilic block copolymer, forming stable inclusion complexes. This invention specifically limits the mass ratio of the amphiphilic block copolymer to the cyclodextrin compound to 1:0.5 to 1:2.0. This specific ratio effectively matches the number of cavities to the length of the hydrophobic segments at the molecular scale, avoiding both the release of amphiphilic polymers due to insufficient cyclodextrin dosage and subsequent water washing loss, and preventing a sharp increase in casting solution viscosity and localized agglomeration within the matrix caused by excessive cyclodextrin. During the solvent-induced phase inversion process, in the assembly formed by combining these optimal ratios, the hydroxyl-rich hydrophilic outer surface of the cyclodextrin can not only form a hydrogen-bonded interwoven network with the hydrophilic segments of the amphiphilic block copolymer, but also generate strong hydrogen-bonded interactions with the matrix polymer, such as polyethersulfone or polysulfone. This microscopic synergistic mechanism, based on molecular-level assembly and precise ratio control, allows the originally water-soluble amphiphilic block copolymer to be firmly and uniformly anchored in the porous support layer skeleton.

[0018] Compared with the prior art, the present invention has the following beneficial effects: First, based on inclusion and hydrogen bond anchoring mechanisms, this invention effectively solves the industrial problem of easy loss of hydrophilic additives in porous support layers. Through the aforementioned synergistic network at the molecular level, the tendency of amphiphilic polymers to lose water solubility is greatly restrained. Experimental tests show that, compared to the comparative composite membrane with only pure amphiphilic block copolymers, the composite membrane of this invention exhibits a pure water flux attenuation rate of less than 5% after continuous cross-flow filtration for up to 30 days, demonstrating excellent hydrophilic durability and pore stability.

[0019] Secondly, this invention achieves a simultaneous improvement in water flux and retention performance by interfacially controlling the monomer diffusion rate. The cyclodextrin firmly bonded to the porous support layer not only promotes perfect aqueous phase spreading, but its cavity structure also adsorbs and retains amine monomers, enabling a slow and uniform release of monomers to the water-oil interface and avoiding localized explosive diffusion. Experiments show that this in-situ generated polyamide separation layer is more dense and smooth. In the embodiments of this invention, the composite membrane maintains a high retention rate of over 99.0%, while increasing water flux by 20% to 35% compared to the unmodified control.

[0020] Finally, this invention significantly enhances the delamination and peel resistance of the polyamide composite membrane. Thanks to the dense and uniform hydroxyl-rich network on the surface of the porous support layer, a deep physical interlocking and dense hydrogen-bonded interface is formed between the polyamide separation layer and the support layer. Extreme ultrasonic testing results show that after 30 minutes of high-intensity ultrasonic oscillation treatment, the retention rate reduction of the composite membrane in this invention's embodiments is strictly controlled within 4 percentage points, while the retention rate of the comparative embodiment prepared with conventional substrate membranes shows a drastic decrease of over 32 percentage points. This invention completely avoids membrane blistering and detachment defects, significantly extending the actual service life of the membrane element. Attached Figure Description

[0021] Figure 1 This is a line graph showing the change of water contact angle of the porous support layer obtained in Examples 1-3 and Comparative Examples 1-3 of the present invention with dynamic water washing time.

[0022] Figure 2 The graph shows the normalized water flux variation of the polyamide composite membranes obtained in Examples 1-3 and Comparative Examples 1-3 of this invention under continuous cross-flow operation for 30 days.

[0023] Figure 3 This is a bar chart comparing the retention rates of the polyamide composite films obtained in Examples 1-3 and Comparative Example 1 before and after ultrasonic vibration treatment. Detailed Implementation

[0024] The technical solution of the present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are only used to illustrate the technical principles and macroscopic performance of the present invention, and are not intended to limit the scope of protection of the present invention.

[0025] The polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymers used in Examples 1-3 and Comparative Example 2 of this invention are Pluronic F127 with an average molecular weight of 12600.

[0026] Example 1

[0027] A method for preparing a peel-resistant polyamide composite film with high interfacial adhesion includes the following steps: S1, 16.0 wt% polyethersulfone, 2.0 wt% polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, and 2.0 wt% β-cyclodextrin were dissolved in 80.0 wt% N-methylpyrrolidone. The mixture was mechanically stirred at 60 °C for 12 h until completely dissolved and allowed to stand to remove bubbles, yielding a blended casting solution. At this point, the mass ratio of the amphiphilic block copolymer to the cyclodextrin compound was 1:1.

[0028] S2, the blended casting solution was uniformly coated onto a polyester nonwoven fabric substrate at room temperature with a doctor blade gap of 150 μm. It was then rapidly immersed in a deionized water coagulation bath at 25 °C to undergo solvent-induced phase transformation and film formation. After removal, it was soaked in deionized water for 24 h to obtain a modified porous support layer.

[0029] S3, a 0.5 wt% piperazine aqueous solution was coated onto the surface of the modified porous support layer. After standing for 2 min, the excess aqueous phase was poured off, and the surface moisture was blotted dry with absorbent paper. Subsequently, a 0.15 wt% trimesoyl chloride-hexane solution was brought into contact with the surface of the modified porous support layer and reacted for 30 s. The excess organic phase was then poured off. Finally, the membrane was heat-treated in an oven at 80 ℃ for 5 min to obtain a peel-resistant polyamide composite membrane with high interfacial adhesion.

[0030] Example 2

[0031] A method for preparing a peel-resistant polyamide composite film with high interfacial adhesion includes the following steps: S1, 16.0 wt% polyethersulfone, 2.0 wt% polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, and 1.0 wt% β-cyclodextrin are dissolved in 81.0 wt% N-methylpyrrolidone to obtain a blended casting solution. At this point, the mass ratio of the amphiphilic block copolymer to the cyclodextrin compound is 1:0.5.

[0032] The preparation steps for S2 and S3 are the same as in Example 1, resulting in a peel-resistant polyamide composite film with high interfacial bonding strength.

[0033] Example 3

[0034] A method for preparing a peel-resistant polyamide composite film with high interfacial adhesion includes the following steps: S1, 16.0 wt% polyethersulfone, 1.5 wt% polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, and 3.0 wt% hydroxypropyl-β-cyclodextrin were dissolved in 79.5 wt% N,N-dimethylformamide to obtain a blended casting solution. At this point, the mass ratio of the amphiphilic block copolymer to the cyclodextrin compound was 1:2.0.

[0035] The preparation steps for S2 and S3 are the same as in Example 1, resulting in a peel-resistant polyamide composite film with high interfacial bonding strength.

[0036] Comparative Example 1 A method for preparing a conventional polyamide composite film, the basic steps of which are the same as those in Example 1, the only difference being that: the casting solution in step S1 consists only of 16.0 wt% polyethersulfone and 84.0 wt% N-methylpyrrolidone, without the addition of amphiphilic block copolymer and β-cyclodextrin.

[0037] Comparative Example 2 A method for preparing a composite membrane modified solely by an amphiphilic block copolymer follows the same basic steps as in Example 1, except that: the casting solution in step S1 does not contain β-cyclodextrin, but only adds 4.0 wt% of a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer and 16.0 wt% of polyethersulfone, which are dissolved in 80.0 wt% of N-methylpyrrolidone to obtain a blended casting solution.

[0038] Comparative Example 3 A method for preparing a composite membrane modified solely by cyclodextrin follows the same basic steps as in Example 1, except that the casting solution in step S1 does not contain amphiphilic block copolymers, but only 4.0 wt% of β-cyclodextrin and 16.0 wt% of polyethersulfone are added and dissolved in 80.0 wt% of N-methylpyrrolidone to obtain a blended casting solution.

[0039] The performance testing method is as follows: Basic structure and initial separation performance testing: The porosity of the modified porous support layer was determined using the wet-dry gravimetric method; the initial pure water flux and initial MgSO4 rejection rate of the composite membrane were determined using a standard cross-flow filtration device. The test solution was a 2000 mg / L MgSO4 aqueous solution, the operating pressure was 0.5 MPa, and the test temperature was 25 ℃. The static data for this part are summarized in Table 1.

[0040] Dynamic hydrophilic stability test: The porous support layer was immersed in a constant-temperature deionized water bath with magnetic stirring for dynamic water washing. It was removed and dried at regular intervals, and the surface pure water contact angle was measured to examine the additive's anti-leakage performance. The dynamic changes in water contact angle over 30 days for each embodiment and comparative example are plotted in the appendix. Figure 1 .

[0041] Long-term cross-flow stability test: The cross-flow filtration device was continuously pressurized for 30 days. Water flux was recorded periodically, and the normalized water flux retention rate was calculated to evaluate the pressure resistance of the pores and membrane layer. The time decay curves for each embodiment and comparative example are plotted in the appendix. Figure 2 .

[0042] Extreme ultrasonic peel test: The polyamide composite membrane was immobilized in deionized water and continuously treated in an ultrasonic cleaner with a frequency of 40 kHz and a power of 100 W for 30 min. The retention rate after treatment was then measured to visually assess the interfacial peel strength. A comparison of the retention rates of each example and comparative example before and after ultrasonic treatment is shown in the appendix. Figure 3 .

[0043] Table 1 Summary of Basic Structure and Initial Separation Performance Data of Composite Membranes for Each Group

[0044] Based on the basic data in Table 1 and the appendix Figures 1-3 The results of dynamic and destructive testing are used to analyze the beneficial effects of the present invention in detail: First, as shown in Table 1, the initial pure water flux and support layer porosity of Examples 1-3 are significantly better than those of Comparative Example 1, which was prepared using a traditional pure polyethersulfone substrate. This indicates that the synergistic effect of the amphiphilic block copolymer and cyclodextrin effectively improves the film-forming thermodynamic process and constructs a high-porosity water flow channel. Meanwhile, the initial rejection rate of all examples is consistently above 98.4%, proving that the substrate can perfectly control the interfacial polymerization reaction. Furthermore, it is noteworthy that the initial MgSO4 rejection rate of Comparative Example 3 is only 95.4%. This is because the lack of block copolymer coordination within the support layer matrix leads to the local aggregation of excess and free cyclodextrin on the substrate surface. The resulting physical barrier effect interferes with the uniform distribution of amine monomers in the early stages of interfacial polymerization, resulting in microscopic crosslinking defects in the generated polyamide layer.

[0045] Based on this high initial performance, additional Figure 1 With appendix Figure 2 This further verifies the superior stability of the present invention. For example... Figure 1 As shown, in Comparative Example 2, representing traditional single modification, the water contact angle increased significantly from 45.3° to 72.9° during continuous dynamic washing, indicating that the block copolymer lacking anchoring is easily lost. In contrast, the water contact angle evolution curves of Examples 1-3 are all extremely flat. Example 1 only fluctuated slightly from 38.2° to 41.5° after 30 days of washing, while Examples 2 and 3 are similarly closely distributed in the low contact angle range.

[0046] This excellent resistance to leakage is directly reflected in Figure 2 In macroscopic fluid dynamics properties. For example... Figure 2As shown, due to the complete anchoring of the hydrophilic network, the pores of the support layer in Examples 1-3 did not collapse, and their normalized water flux decay curves converged closely in the upper region of the graph. The flux retention rate remained above 91.4% after 30 days of continuous cross-flow. Meanwhile, Comparative Example 1, lacking any hydrophilic modification, consistently exhibited extremely low absolute water flux values. Comparative Example 3, due to the inability of the single cyclodextrin to form an effective physical anchor, continuously dissolved, leading to pore structure instability, and its normalized flux decayed to 82.7%. Conversely, Comparative Example 2, experiencing severe loss, saw its flux rapidly and continuously decay to 75.2%. These graphs cross-reference the subject-object recognition mechanism at specific ratios, successfully overcoming the industrial pain point of easily soluble additives.

[0047] Regarding the most critical issue of membrane peeling, attached... Figure 3 This provides the most direct evidence of destructive testing. After 30 minutes of high-intensity ultrasonic oscillation, the retention rate of Comparative Example 1 dropped catastrophically to only 65.9%, indicating that its polyamide release layer and hydrophobic inert substrate are only weakly physically attached, making it extremely prone to large-area delamination. In contrast, the retention rates of Examples 1-3 remained at 97.4%, 94.6%, and 96.5% respectively after ultrasonic treatment, with the decrease strictly controlled within 4 percentage points, far superior to the drastic attenuation of over 32 percentage points in Comparative Example 1. This result irrefutably proves that the cyclodextrin and block copolymer distributed on the surface of the porous support layer jointly construct dense hydroxyl-rich anchoring points. Through dense hydrogen bonds and physical interlocking, the polyamide release layer is firmly locked to the support layer surface, giving the composite membrane unparalleled delamination resistance and peel resistance.

[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a peel-resistant polyamide composite film with high interfacial adhesion, characterized in that, Includes the following steps: S1, the matrix polymer, amphiphilic block copolymer and cyclodextrin compound are mixed and dissolved in an organic solvent to obtain a blend casting solution; S2, the blended casting liquid is coated onto the substrate, and then placed in a coagulation bath to undergo a non-solvent-induced phase transformation to form a film, thereby obtaining a modified porous support layer; S3, an aqueous solution containing amine monomers is coated onto the surface of the modified porous support layer. After removing the excess aqueous solution, the surface of the modified porous support layer is brought into contact with an organic solution containing acyl chloride monomers to undergo an interfacial polymerization reaction to generate a polyamide separation layer. The polyamide composite film with high interfacial bonding strength is obtained after heat treatment.

2. The method for preparing the high interfacial bonding strength peel-resistant polyamide composite film according to claim 1, characterized in that, The matrix polymer is selected from polyethersulfone or polysulfone; the organic solvent is selected from one or more of N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide.

3. The method for preparing the high interfacial bonding strength peel-resistant polyamide composite film according to claim 1, characterized in that, The amphiphilic block copolymer is a poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer; the cyclodextrin compound is selected from one or more of β-cyclodextrin, hydroxypropyl-β-cyclodextrin or methyl-β-cyclodextrin.

4. The method for preparing the high interfacial bonding strength peel-resistant polyamide composite film according to claim 1, characterized in that, The mass fraction of each component in the blend casting solution is as follows: 12-20 wt% of the matrix polymer, 0.5-5.0 wt% of the amphiphilic block copolymer, 0.5-5.0 wt% of the cyclodextrin compound, and the balance being the organic solvent; the mass ratio of the amphiphilic block copolymer to the cyclodextrin compound is 1:0.5-1:2.

0.

5. The method for preparing the high interfacial bonding strength peel-resistant polyamide composite film according to claim 1, characterized in that, In step S2, the substrate is polyester nonwoven fabric; the coagulation bath is deionized water, and the temperature of the coagulation bath is 15~30℃.

6. The method for preparing the high interfacial bonding strength peel-resistant polyamide composite film according to claim 1, characterized in that, Before step S3, the modified porous support layer obtained in step S2 is immersed in deionized water for 12-48 hours to wash away residual solvent on the surface.

7. The method for preparing the high interfacial bonding strength peel-resistant polyamide composite film according to claim 1, characterized in that, The amine monomer in the aqueous solution is selected from one or more of piperazine, m-phenylenediamine, or p-phenylenediamine; the acyl chloride monomer in the organic solution is trimesoyl chloride; and the solvent in the organic solution is selected from one or more of n-hexane, isoalkanes, or n-heptane.

8. The method for preparing the high interfacial bonding strength peel-resistant polyamide composite film according to claim 1, characterized in that, The mass fraction of the amine monomer in the aqueous phase solution is 0.1~2.0 wt%; the mass fraction of the acyl chloride monomer in the organic phase solution is 0.05~0.5 wt%.

9. The method for preparing the high interfacial bonding strength peel-resistant polyamide composite film according to claim 1, characterized in that, In step S3, the contact time between the aqueous solution containing amine monomers and the modified porous support layer is 1-5 min; the contact time between the organic solution containing acyl chloride monomers and the modified porous support layer is 10-60 s; the temperature of the heat treatment is 60-100 ℃, and the heat treatment time is 2-10 min.

10. A peel-resistant polyamide composite film with high interfacial adhesion prepared by the preparation method according to any one of claims 1 to 9, characterized in that, The high interfacial bonding strength peel-resistant polyamide composite membrane includes a modified porous support layer and a polyamide separation layer bonded to the surface of the modified porous support layer; the modified porous support layer contains the amphiphilic block copolymer and the cyclodextrin compound blended within its matrix.